Polymerase chain reaction in viral anterior uveitis with secondary glaucoma: Analysis of 28 eyes from a tertiary eye care center in South India - Bhavini Johri; Dhanurekha Lakshmipathy; Jyotirmay Biswas (Taiwan Journal of Ophthalmology)
PURPOSE: To study the role of polymerase chain reaction (PCR) in viral anterior uveitis with secondary glaucoma. MATERIALS AND METHODS: This was a retrospective cohort study in which aqueous humor from 28 eyes of 23 patients with viral uveitis and secondary glaucoma from 2008 to 2024 was sent for real-time/nested PCR. The clinical features of the patients were analyzed (P < 0.05 statistically significant). RESULTS: The median age at uveitis onset was 45 years. Secondary open-angle glaucoma was found in 23 out of 28 eyes, 82.1%. The median intraocular pressure (IOP) reduced significantly from baseline, 18.5 to 14 mmHg at the final visit (P = 0.01). Maximum IOP was 60 mmHg. PCR was positive in 57.1% of eyes, mostly for varicella-zoster virus (32.1%), followed by Cytomegalovirus (CMV) (17.8%) and herpes simplex virus (10.7%). Valacyclovir was used to treat 50% of eyes. CMV was treated with valganciclovir (10.7% eyes). Antiglaucoma and anti-inflammatory medications were reduced significantly from initiation (P < 0.001). CONCLUSION: PCR enables timely and accurate detection of virus causing anterior uveitis and helps salvage vision in secondary glaucoma with appropriate antiviral therapy.